2019
DOI: 10.1038/s12276-019-0207-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial superoxide dismutase 2 mediates γ-irradiation-induced cancer cell invasion

Abstract: Sublethal doses of γ-rays promote cancer cell invasion by stimulating a signaling pathway that sequentially involves p53, sulfatase 2 (SULF2), β-catenin, interleukin-6 (IL-6), signal transducer and activator of transcription 3 (STAT3), and Bcl-XL. Given that Bcl-XL can increase O2•− production by stimulating respiratory complex I, the possible role of mitochondrial reactive oxygen species (ROS) in γ-irradiation-induced cell invasion was investigated. Indeed, γ-irradiation promoted cell invasion by increasing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 34 publications
1
19
0
2
Order By: Relevance
“…In a previous study, a reduction in ROS generation in X-ray-treated cancer cells did not increase cell death (Wang and Zhang 2019). Moreover, γ -ray irradiation can induce cancer cell invasion by increasing ROS generation and decreasing SOD activity (Jung et al 2019). These observations indicate that the context-dependent functions of ROS in cell survival and death might be associated with the different species and levels of intracellular ROS (Kuwabara et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…In a previous study, a reduction in ROS generation in X-ray-treated cancer cells did not increase cell death (Wang and Zhang 2019). Moreover, γ -ray irradiation can induce cancer cell invasion by increasing ROS generation and decreasing SOD activity (Jung et al 2019). These observations indicate that the context-dependent functions of ROS in cell survival and death might be associated with the different species and levels of intracellular ROS (Kuwabara et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Cell culture and treatments. Sources and authentication of HCT116 colon cancer cells, their p53-or p21-knockout variants, H460 and A549 lung cancer cells have been described previously (17,18). Cells were regularly screened for mycoplasma contamination using MycoAlert Mycoplasma Detection Kits (Lonza, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…12 Moreover, it is reported that increased SULF2 from sublethal doses of IR regulates IR-induced cancer cell invasion via mitochondrial superoxide dismutase 2 (SOD2). 13 These results suggest that IR promotes cancer cell invasion by activating different signaling pathway mediators, such as Bcl-X L , NF-κB, and SOD2.…”
mentioning
confidence: 88%